Digital Technology and Firm Performance in IT Services: The Mediating Role of Technology Value Customization - Romy Pramono; Thomas Stefanus Kaihatu; Denny Bernardus; Halek Mu'min (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines whether Technology Value Customization (TVC) mediates the effects of Digital Technology (DT), Dynamic Capability (DC), and Customer Orientation (CO) on Firm Performance (FP) in Indonesia's IT services industry, drawing on Dynamic Capability Theory and Service-Dominant Logic. Design/Methodology/Approach – Data from 240 IT service firms in Jakarta, Surabaya, and Bandung were collected via a seven-point Likert questionnaire and analyzed using PLS-SEM (5,000-subsample bootstrapping), Necessary Condition Analysis (NCA), and Confirmatory Tetrad Analysis. Findings/Results – DT and DC had no significant direct effect on FP, while CO's direct effect and all paths to and from TVC were significant. The DT-FP and DC-FP relationships showed statistically significant indirect-only associations via TVC (consistent with, though not definitive proof of, full mediation per Zhao et al., 2010), while CO-FP showed a complementary partial-mediation pattern; NCA identified CO, DT, and TVC as necessary conditions for FP, while DC was not. Originality/Value – TVC offers a plausible mechanism reconciling prior inconsistent findings on technology's direct effect on performance, integrating Service-Dominant Logic with Dynamic Capability Theory. The key implication is that technological resources drive performance only when customized into customer-relevant value.